2023
DOI: 10.26434/chemrxiv-2022-1v5b4-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced Coherence by Coupling Spins through a Delocalized π-System: Vanadyl Porphyrin Dimers

Abstract: Vanadium(IV) magnetic centers are prime candidates as molecular quantum units. One longstanding question is how to obtain a scaffold that connects multiple centers and allows two communication modalities: magnetic and electronic. We have synthesized and studied a selection of vanadyl porphyrin dimers, as models of the most synthetically accessible linear porphyrin arrays. We show that a strongly π-conjugated backbone places the magnetic system in the strong coupling regime and protects the quantum coherence ag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…T m values of 8 are instead slightly faster than those of 6 and 7 and also lower than those reported for dimeric V IV O bimetallic complexes, including the homometallic vanadyl porphyrin dimer. [11,22,49,50] The accurate determination of the Spin-Hamiltonian parameters of 8 allows us to envision the microwave operation of the dimeric unit as a C-NOT quantum gate. This is fundamental for realizing a universal quantum computer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…T m values of 8 are instead slightly faster than those of 6 and 7 and also lower than those reported for dimeric V IV O bimetallic complexes, including the homometallic vanadyl porphyrin dimer. [11,22,49,50] The accurate determination of the Spin-Hamiltonian parameters of 8 allows us to envision the microwave operation of the dimeric unit as a C-NOT quantum gate. This is fundamental for realizing a universal quantum computer.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, surface-induced reactivity has been exploited to produce flat triply-linked porphyrin nano tapes. [16][17][18] Studies on the exchange-coupling in porphyrin metal dimers evidenced moderate antiferromagnetic interactions promoted by the conjugation in doubly-and triply-linked porphyrins, [19][20][21][22][23] while meso-meso singly-linked homometallic Cu II dimers exhibit negligible exchange interactions. [19] We recently demonstrated that the vanadyl analog shows a measurable exchange interaction of the order of 10 À 2 cm À 1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations